IDEASIONAL FUNCTION TRANSITIVITY IN THE TEXT OF DAQAAIQUL AKHBAR: SYSTEMIC FUNCTIONAL LINGUISTIC STUDY - Juramli, J (International Journal of Systemic Functional Linguistics, 2017)
This paper reports condition of transitivity system of ideational function realized in the text of Daqaaiqul Akhbar, as a useful form of local cultural text that can nurture creativity of Sasak ethnic group. Investigation in this research was carried out with some focuses as fomulated in the research questions, such as 1) âWhat is the most dominant type of transitivity system realized in the text of Daqaaiqul Akhbar "Khabar Nature News Hereafter?â; 2) âHow is the relevance of the findings with discourse learning in high school?â The purpose of this study was to describe the most dominant type of transitivity system Daqaaiqul Akhbar text and to illustrate the relevance of the findings with discourse learning in senior high school. The investigation was conducted with the application of combination research approach of qualitative and quantitative research approach. Qualitative research approach refers to the basic assumptions as the best effort to gain an understanding of the phenomena. Data of the research was collected with utilization of observation, documentation and record method. The result shows that types of transitivity system found in text of Daqaaiqul Akhbar, which consists of 86 clauses including process items 84 (78.83%), participant 149 items (140.21%), and circumstance 87 items (81.79%). Relevance of the findings with discourse learning in senior high school is, 1) text of Daqaaiqul Akhbar can be a reference that explores the values (value) related learning objectives achievement. Discourse can analyzed based on character in Curriculum 2013, 2). Examination of the text of discourse in high school is not monotonous on the view of structural grammar (conventional) which is still at the traditional level.